Singular Point Detection for characterization of polycrystalline permanent magnets. (August 2020) - Cabassi, R.
Abstract: Magnetic anisotropy is among the most important properties that are to be measured in permanent magnet characterization. While in single crystals it can be quite straightforwardly evaluated by conventional magnetometry, it often is of uncertain determination when dealing with polycrystalline samples. Singular Point Detection (SPD) is a special technique aimed at solving this particular problem. SPD has been developed starting from the 70s of last century and, in spite of being an old technique, it still is an up to date tool able to give reliable and quick results in many problematic situations. In this paper the theoretical and experimental aspects of SPD are first reviewed, then some examples of recent results are shown.